MENINGKATKAN KETERAMPILAN PUBLIC SPEAKING SISWA MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY (TS-TS) PADA KELAS V SDN 06 SELONG TAHUN AJARAN 2024/2025 - Hirliana, Wiwinda; Andiniati, Mauly Rizki; Jannah, Raudatul; Muspita, Zalia; Ernawati, Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to apply Two Stay Two Stray (TS-TS) learning model to increase 5th grader students’ public speaking skill at SD Negeri 6 Selong. This research uses classroom action research has four stages in application, those are: planning, action, observation, and reflection. This research has two cycles, those are cycle I and cycle II. Each cycle shows an increase in every aspect of public speaking skills, including aspects of grammar, courage, fluency and mastery of the material. The results of the first cycle of research on the grammar aspect had an average score of 2.12, the courage aspect had an average score of 1.91, the fluency aspect had an average score of 2.24, and the material mastery aspect had an average score of 1.84.Furthermore, there was an increase in the average score for each aspect of public speaking skills in cycle II where the average score for the grammar aspect was 2.54, the courage aspect had an average score of 2.39, the fluency aspect had an average score of 2.55, and the material mastery aspect had average score 2.40. So it can be concluded that the research results show an increase in public speaking skills in class V students at SDN 6 Selong with the Two Way Two Stray (TS-TS) model.